Tests for the antibacterial and anti-inflammatory potential of the Asem Tengger plant (Radicula armoracia Robinson) obtained from the ethnomedicine study in the Tengger tribe - Yaya Sulthon Aziz; Rony Setianto; Tatiana Siska Wardani; Nurul Nurhayati; Belinda Arbitya Dewi (LPPM Universitas Duta Bangsa Surakarta, 2021)
Purpose: Local wisdom, especially in the Tengger Bromo tribe, East Java makes a potential that must be developed sustainably. The Asem Tengger plant (Radicula armoracia Robinson) is a plant that has antibacterial and anti-inflammatory potential in the Tengger tribe. This plant has high ICF and UV values. This study aims to determine the types of plants that have been used by the Tengger Tribe have antibacterial and anti-inflammatory activities with the dilution method and in vitro cell membrane stability. Methodology: Samples were taken from the Tengger Bromo Probolinggo Tribe, extracted by maceration using 95% ethanol. Characterization includes non-specific parameters and specific parameters. Identification of chemical contents includes flavonoids, glycosides, saponins, alkaloids. Antimicrobial test by dilution method, each concentration was tested on Staphylococcus aureus ATCC 2592, Bacillus subtilis ATCC 6633, Pseudomonas aeruginosa ATCC 27853, Salmonella typhi ATCC 13311, and Candida albicans ATCC 10231. The anti-inflammatory activity test using ethanol extract from muscle flour was made up to a concentration of 250 ppm, 500 ppm, 1000 ppm, and 2000 ppm with the in vitro anti-inflammatory test with the human red blood cell (HRBC) method. Results: Based on the antimicrobial test, Asem Tengger has the potential to be antibacterial to Staphylococcus aureus ATCC 2592 in the water and n-hexane fractions with a value of 2.5% MBC. The anti-inflammatory test showed the results of membrane stability of 57.97% from a concentration of 2000 ppm which shows a number that has the potential to be a reference for potential medicinal plants. Value: The Asem Tengger plant used by the Tengger tribe has the potential as new antimicrobials and anti-inflammatory